International Islamic Center Di Surakarta Dengan Penekanan Pada Arsitektur Modern Kontemporer - anam, khoirul, Dr. Ir. W. Nurjayanti, MT, Ir. Samsudin Raidi, MSc (2016)
International Islamic Center in Surakarta With Emphasis On Architecture Contemporary is a center of science, technology and the propagation of Islam that are used for religious activities, international standard which is located in Surakarta with emphasis on form follow function (form follows function) with designs that present a more advanced, varied, flexible, and innovative. Planning International Islamic Center is intended to accommodate several activities supporting Islamic comprising mu'amalah activities, propaganda and Islamic study groups that followed the era of modernity include knowledge of technology developed at this time. Designing Islamic Center by embracing activities, needs and facilities located abroad (international), which aims to realize a container of educational activities, technology development, and the preaching of Islam, as a central hub that is informative, educative for the people in Surakarta in particular and visitors in general. Discussion on the concept of the International Islamic Center With Emphasis On Modern Contemporary Architecture will be applied to the planning and design spatial pattern of spatial relations, and function space. While planning and design style of the building, landscaping and interior use of the concept of Modern Contemporary Architecture at the moment.